Comorbidities in patients with gout prior to and following diagnosis: case-control study - Kuo, Chang-Fu; Grainge, Matthew J.; Mallen, Christian; Zhang, Weiya; Doherty, Michael (BMJ Publishing Group, 2016)
OBJECTIVES: To determine the burden of comorbidities in patients with gout at diagnosis and the risk of developing new comorbidities post diagnosis.